Participación del acompañante en el cuidado del paciente hospitalizado. Instituciones de segundo nivel. Área Metropolitana. Medellín 1999-2000 (2002)
ABSTRACT: Descriptive traversal study to identify the opportunities given by the nursing team conducive to familiar attendants echo participate in the care the hospitalized relatives. It’s an answer to the continuous questions from the academic experiences with hospitalized relatives. One structured interview soar realized to 265 attendants of hospitalized person in institutions of second level of attention; it searched the socio-demographics aspects of the patient and the attendant, and which are indicated, explained and supported by the nursing team; the education given to the attendants is another factor orbed to persons included in the sample. Those hospitalized persons with attendants, 54% are female, in the age group of 64-77 years, with low scholarly. The first cause of morbidity corresponds to gastrointestinal problems, followed by cardiovascular diseases. The attendants are usually the daughters with a median age of 45 years. The tasks more frequently realized by attendants are those related to subsistence, such as bathing and feeding, others as lecture, games and music are realized only by 10% of the attendants; conversation is the task more frequently realized. The interaction of the nursing team with the attendants is almost inexistent for all the task of caring explored in the study, except for the indication and support given for the bath. The practical nurse has more interaction with the attendants. It’s remarkable the absence of professional nurse, but just to 11% of the hospitalized persons. It’s only penetrating in the mystery of care and searching deep in the human and cultural character of care, how we can transcend a respectful and trustful relation with the clients, families and the social environment.